A qualitative exploration of Communities of Practice within a multi-partner organisation supporting health and care research - Abrahamson, Vanessa; Richardson, Lisa; Brookes, Nadia (Advanced Journal of Professional Practice, 2026)
Background: Communities of practice (CoPs) are increasingly recognised as mechanisms for research co-production and implementation within health and social care systems. The National Institute for Health and Care Research Applied Research Collaboration is a multi-organisational partnership bringing together healthcare providers, universities, local authorities and voluntary organisations to support applied research that meets local needs. This paper reports a qualitative evaluation of CoPs supported by the Applied Research Collaboration Kent Surrey Sussex, with the overarching aim of exploring their development, functioning and perceived impact, to inform strategies for sustaining and optimising CoPs in health and social care research and practice. Method: A preparatory phase included a scoping review, confirmation of active CoPs and appraisal of available documentation. The study adopted a realist paradigm and was co-designed with three public contributors. Semi-structured online interviews were conducted with 23 participants (strategic leads, CoP facilitators, researchers, practitioners and public contributors), April–June 2024, using topic guides informed by the literature and Wenger’s framework. Data were analysed thematically following Bazeley’s iterative, realist-aligned approach. Results: We identified three themes focused on operationalising the CoPs and negotiating inherent tensions (online versus in-person, small versus large groups, narrow versus broad remit, open-ended or finite timeframe); the work involved in maintaining and sustaining CoPs; and delivering/monitoring outcomes, mostly related to networking and learning new knowledge, shared with partner organisations. Smaller project specific CoPs were better able to facilitate research implementation in a clearly defined area and bridge from research into practice. Conclusion and recommendations: CoPs in multi-organisational settings require dedicated support for facilitators, including protected time and resources. Member organisations should recognise the value of CoPs and enable practitioners and researchers to participate. Co-designing aims and expectations with all members, including public contributors, and agreeing on measurable outcomes from the start are essential for ensuring relevance, inclusivity, and impact.